The identification and pharmacological evaluation of potent, selective and orally available ACC1 inhibitor. Issue 23 (1st December 2019) - Mizojiri, Ryo; Asano, Moriteru; Sasaki, Masako; Satoh, Yoshihiko; Yamamoto, Yukiko; Sumi, Hiroyuki; Maezaki, Hironobu
Graphical abstract: Abstract: In our effort to explore the potential of ACC1-selective inhibitor as in vivo probe molecule, a series of 1, 3-benzoxazole derivatives was synthesized. Previously, we reported a series of novel bicyclic and monocyclic ACC1-selective inhibitors. Among them, compound 1a exhibited highly potent cellular activity (acetate uptake IC50  = 0.76 nM) as well as promising in vivo PD efficacy. However, compound 1a caused severe body weight reduction in repeated dose administration in the mouse model. Since 1a showed potent inhibitory activity against mouse ACC1 as well as strong inhibition of mouse ACC2, we further examined a series of 1a analogues in order to reduce undesirable body weight change. The replacement of acetamide moiety with ureido moiety dramatically improved selectivity of mouse ACC1 against ACC2. In addition, analogue 1b displayed favorable bioavailability in mouse cassette dosing PK study, hence in vivo PD studies were also carried out. Oral administration of 1b significantly reduced the concentration of malonyl-CoA in HCT-116 xenograft tumors at doses of more than 30 mg/kg. Furthermore, compound 1b showed significant antitumor efficacy in 786-O xenograft mice at an oral dose of 30 mg/kg (T/C = 0.5%). Accordingly, our novel potent ACC1-selective inhibitor represents a set of useful orally-available research tools, as well as potential therapeutic agents particularly in terms of new cancer therapies.